Anti‐Dehydration and Rapid Trigger‐Detachable Multifunctional Hydrogels Promote Scarless Therapeutics of Deep Burn. (1st February 2023) - An, Heng; Zhang, Meng; Zhou, Liping; Huang, Zhe; Duan, Yongchao; Wang, Cheng; Gu, Zhen; Zhang, Peixun; Wen, Yongqiang
Abstract: There are issues and challenges in treating deep burns because of the long recovery time, frequent dressing changes, wound infection, and easy to form scar that influence aesthetics. Besides, some specific tissues are not suitable for large dressing coverage (e.g., face, perineum). Therefore, an ideal deep burn dressing should have good adhesion properties to fit the wound effectively, painless and quick replacement, resistant to infection, accelerate wound healing, reduce scarring and facilitate monitoring and diagnosis. Herein, an anti‐dehydration and rapid‐trigger multifunctional hydrogel dressing is prepared by interface reaction. The Pacrylamide‐Formylboronicacid‐Tannic acid (PAFT) hydrogels are prepared by a simple method on anti‐dehydration elastomeric membrane, which is obtained using tannic acid as a dynamic cross‐linking agent with 3‐formylboronic acid and acrylamideunder UV light. The hydrogel exhibits a strong interfacial adhesion (892 J m −2 ± 65 J m −2 ), which rapidly (2 min) decreases (to 180 J m −2 ± 20 J m −2 ) when in the presence of glucose solution. The hydrogel has excellent anti‐dehydration and moisturizing properties, and also exhibits superior antibacterial properties, hemostasis, and biocompatibility. This hydrogel is transparent allowing effective observation of wound transformation and therapeutics. Moreover, PAFT hydrogel accelerates the healing of deep burns and reduces scars. Abstract : The optimal multifunction Pacrylamide‐Formylboronicacid‐Tannic acid (PAFT) hydrogel dressing that integrates anti‐dehydration, reduces scar, trigger‐detachable and transparent can solve the problems of scarring, slow recovery, high risk of infection, and frequent replacement in deep burns. The PAFT hydrogel dressings can be customized in different colors and shapes and used on specific tissue (face) to achieve cosmetic results.